Mathematical analysis of cost function and reliability condition for new proposed multilevel inverter topology - D. Karthikeyan; K. Vijayakumar; D. Senthil Kumar; Daki Krishnachaitanya (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In this paper cost function and reliability analysis of classic novel symmetric multilevel inverter topology has been presented. Cost function and reliability analysis are the economical factors of the effieciency of an inverter, this made the intrest in this area.cost function deneotes the cost of the inverter based on the power flow, reliability explain the mean time failure propotional to the life span. Firstly the cost function of the novel topology has been proposed using mathematical calculation using various current rating and the results are validated compared with exiting topology. Secondly reliability approach is used to evaluate the reliability of the switch with respect to the failure rate and mean time period of the switch using fedis and markow reliability analysis equations and the results are evaluated for all the switches present in the topology. And the results are the compared with the conventional multilevel inverter, cost function and reliability analysis of the proposed multilevel inverter.